DIETHYLENE GLYCOL POISONING IN NIGERIAN CHILDREN - Osinusi K; Sodeinde O; AMBEJ P; NJINYAMM N; AKANGEE U; SPIEGEL RA; AGHADIUNO PU (Nigerian Journal of Paediatrics)
Summary:. Clinical and pathological features in 23 children who developed acute renal failure from what was subsequently proven to be diethylene glycol poisoning are presented. Symptoms of cases included anuria, fever, diarrhoea and vomiting. Eighteen (78.3%) had hepatomegaly, 11 (47.8%) had evidence of respiratory dis tress and 7 (30.4%) had acidotic breathing. Seven (30.4%) of the children were dehydrated on physical examination. Alteration in the level of consciousness was observed in 13 (56.5%) children. The major biochemical abnormalities were acidosis and elevated blood urea nitrogen. Although serum bilirubin was normal in those in whom it was determined, the liver enzymes were elevated in the 2 patients in whom they were determined. Patients were treated as for acute renal failure of renal origin and four children had peritoneal dialysis. Twenty-two (95.6%) of the patients died and outcome was unknown in the remaining patient who was dis charged against medical advice. Autopsies in 7 patients revealed a characteristic nephrotoxic acute tubular necrosis and centrilo bular hepatic necrosis characterized by vacuolar and ballooning degeneration of the metabolically active renal tubular cells and hepatocytes.